MUCINOSIS BUCAL FOCAL - REPORTE DE UN CASO - Dávila Barrios, Lorena; Arteaga Altuve, Susana; Quiñónez Márquez, Belkis; Molina Barreto, Manuel; Castillo Cáceres, Leonel; Florido, Rosalba; Sosa, Lisbeth; González, Erika (Acta Odontológica Venezolana, 2011)
Mucinosis are dermatosis characterised by mucin deposit on the dermis. Mucinosis in the oral cavity are not frequent and until this date 38 cases have been reported in literature. Clinically it is presented as an asymptomatic elevation, of firm consistency, more frequently localized in the gum or alveolar mucous. A 19 year old patient case was reported. He had a voluminous mass with an edema aspect, a smooth surface, localized on the vestibular gum between 23 and 24, firm consistency, painless and with three years evolution, with a pyogenic granuloma or gingival hyperplasia alleged diagnose. After the biopsy sample was taken, the hystopatological study revealed fibrillar processes of a mixoid aspect and inflammatory cell accumulations consisting of neutrophiles, lymphocytes, plasmocytes, polymorphonuclear leukocytes. A focused oral mucinosis and gingivitis was definitively diagnosed. No recurrence was observed after it was removed. KEY WORDS: Mucinosis, focused oral mucinosis, gingival growth, gingival hyperplasia RESUMEN Las mucinosis son dermatosis caracterizadas por el depósito de mucina en la dermis. La mucinosis en la cavidad bucal es poco frecuente y hasta la fecha se han reportado en la literatura 38 casos. Clínicamente se presenta como una elevación asintomática, de consistencia firme, localizada con mayor frecuencia en la encía y en la mucosa alveolar. Se reporta el caso de una paciente de 19 años de edad que presentaba una masa voluminosa de aspecto edematoso, superficie lisa, localizada en la encía vestibular entre 23 y 24, de consistencia firma, indolora y de tres años de evolución, con diagnóstico presuntivo de granuloma piógeno o hiperplasia gingival. El estudio de la biopsia reveló procesos fibrilares de aspecto mixoide y acúmulos de células inflamatorias consistentes en neutrófilos, linfocitos, plasmocitos y leucocitos polimorfonucleares. Se estableció el diagnóstico definitivo de mucinosis bucal focal y gingivitis. No se ha observado recurrencia un año después de su remoción. PALABRAS CLAVE: Mucinosis, mucinosis bucal focal, agrandamiento gingival, hiperplasia gingival.